History of war 50 events you really need to know - Cross, Robin (Quercus, 2012)
Human history - from the empires of the ancient world to the superpowers of the 21st century - has been inextricably shaped by conflict and the weapons that have been used to wage it. The technologies that have produced advanced civilizations have also been harnessed to the grim business of warfare. This short history, stretching from the chariot to the Stuxnet virus which disabled Iran's nuclear enrichment programme in 2007, charts some of the most significant weapons, fortifications and tactics that have been developed in the last 2,500 years. It is a scintillating introduction to the world's most enduring phenomenon. The 50 events include: The Egyptian New Kingdom; Heavy infantry tactics; Grand strategy of Alexander the Great; Naval warfare; Legion versus phalanx; The army on the march; Roman siegecraft; Kingship and command; Cavalry and castles; The age of chivalry; The changing battlefield; Siege trains and siegecraft; The age of Vauban; The age of Frederick the Great; The Seven Years' War; Colonial conflict; Napoleon, tactics and grand strategy; Nelson and naval tactics; The rise of the Dreadnought; Steam and steel; Firepower; Mobilization; Trench warfare; Air warfare; The Manhattan Project and Cyberwar.